PENGUATAN EKONOMI PESANTREN MELALUI MANAJEMEN UNIT USAHA AIDITEL DI PONDOK PESANTREN API SYUBBANUL WATHON SECANG - Setyawan, Hamim (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
This research uses a qualitative descriptive approach because the approach can easily obtain in-depth information. The basic impetus for choosing this method is to answer the role of the Aiditel business unit in developing the economy of the boarding school, data collection techniques through interviews are the techniques used by the author to obtain existing information, and the results of this study are that over time seeing the needs of students and walisantri in communicating so that a telephone shop appears and then from the telephone shop it develops to provide stationery, and until now it continues to develop until the times also make this Aiditel wartel not only provide cellular phones and stationery but also provide video calls via WhatsApp, then the finances from the results of this business are reported regularly to the leadership of the boarding school, which will then be combined with cooperatives and other business units which will be managed directly by Mrs. Nyai for the needs of infrastructure and other needs.